2022
DOI: 10.3390/s22051695
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Estimation of Water Stress in Choy Sum (Brassica chinensis var. parachinensis) Using Integrative Approach

Abstract: To optimize crop water consumption and adopt water-saving measures such as precision irrigation, early identification of plant water status is critical. This study explores the effectiveness of estimating water stress in choy sum (Brassica chinensis var. parachinensis) grown in pots in greenhouse conditions using Crop Water Stress Index (CWSI) and crop vegetation indicators to improve irrigation water management. Data on CWSI and Spectral reflectance were collected from choy sum plants growing in sandy loam so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, these sensors are subject to many environmental factors such as wind speed, rainfall, sunlight, and extreme temperature. In [46], thermal infrared images using WWARIC Workswell Wiris Agro R Infrared Camera (WWARIC) and hyperspectral images using Analytical Spectral Device (ASD) were captured of choy sum for estimating water stress. Results showed that this combined technique is non-destructive and rapid.…”
Section: Infrared Thermal Cameramentioning
confidence: 99%
“…However, these sensors are subject to many environmental factors such as wind speed, rainfall, sunlight, and extreme temperature. In [46], thermal infrared images using WWARIC Workswell Wiris Agro R Infrared Camera (WWARIC) and hyperspectral images using Analytical Spectral Device (ASD) were captured of choy sum for estimating water stress. Results showed that this combined technique is non-destructive and rapid.…”
Section: Infrared Thermal Cameramentioning
confidence: 99%
“…Due to what has been raised, surface temperature measurement through thermographic cameras has been widely used in various fields in recent years (Budzier and Gerlach, 2018). Among the various benefits provided by thermography, its easy handling at the time of capturing the thermal image stands out, as well as its wide spatial resolution in one or several objects simultaneously (Harrap et al, 2018), this involves detecting plant water stress in time, a situation that helps to optimize irrigation with the intention of enhancing the plant to an optimal production, this in the medium term, leads to the economic performance of the plantation, as well as sustainability until the harvest is achieved (Al Aasmi et al 2022).…”
Section: Introductionmentioning
confidence: 99%